ANALYSIS OF THE IMPLEMENTATION PATTERN OF BEHAVIOURISTIC THEORY AND ITS CONTRIBUTION TO THE ACHIEVEMENT OF FIQH LEARNING OBJECTIVES AT MTs DARUL AMIN PALANGKA RAYA CITY - Sayid Ahmad Ramadhan; Mazrur (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to explore the implementation pattern of behaviouristic theory in learning Jurisprudence in class VII at MTs Darul Amin Palangka Raya City and examine its real contribution to the achievement of educational goals. Using a qualitative approach and descriptive-analytical field research method, this study found that the implementation of behaviouristic theory, especially in the topic of Hajj and Umrah, has been able to shape students' learning behaviour systematically through structured stimulus reinforcement. Interestingly, the practice in the field shows an integrative tendency with the principles of constructivistic theory, marked by the existence of discussion space and teacher flexibility in adjusting teaching strategies to the psychosocial dynamics of learners. This finding indicates that although behaviourism focuses on observable behaviour change, in certain contexts it can still synergise with pedagogical approaches that are more humanistic and dialogical.